2014
DOI: 10.1186/1475-2875-13-507
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective metabolism of primaquine by human CYP2D6

Abstract: BackgroundPrimaquine, currently the only approved drug for the treatment and radical cure of Plasmodium vivax malaria, is still used as a racemic mixture. Clinical use of primaquine has been limited due to haemolytic toxicity in individuals with genetic deficiency in glucose-6-phosphate dehydrogenase. Earlier studies have linked its therapeutic effects to CYP2D6-generated metabolites. The aim of the current study was to investigate the differential generation of the CYP2D6 metabolites by racemic primaquine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 34 publications
3
48
0
1
Order By: Relevance
“…The analytic methods for phenotyping the potentially reactive phenolic metabolites of PQ generated with human hepatocytes (Avula et al, 2013) and recombinant human CYP2D6 (Fasinu et al, 2014) have been reported recently and may be applied to clinical studies with individual PQ enantiomers.…”
Section: Discussionmentioning
confidence: 99%
“…The analytic methods for phenotyping the potentially reactive phenolic metabolites of PQ generated with human hepatocytes (Avula et al, 2013) and recombinant human CYP2D6 (Fasinu et al, 2014) have been reported recently and may be applied to clinical studies with individual PQ enantiomers.…”
Section: Discussionmentioning
confidence: 99%
“…Such drugs would be invaluable tools in the fight against malaria. (Fasinu, et al, 2014;Garg, et al, 2011;Pybus, et al, 2012;Vasquez-Vivar & Augusto, 1992, 1994 for further metabolite literature. Unmodified primaquine has little to no liver stage antimalarial activity.…”
Section: The Need For the Development Of Non-cyp 2d6 Metabolized Livementioning
confidence: 99%
“…8 a role in the metabolism that occurs both in vitro and in vivo (Fasinu, et al, 2014;Tekwani, et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The predominant and most thoroughly studied metabolite of PQ is the carboxyl form, carboxyprimaquine (CPQ) (19). PQ also is extensively hydroxylated on the quinoline core (11,16,17,20). The hydroxylated metabolites of PQ at positions 2, 3, and 4 were prepared synthetically as reference standards (see Fasinu et al [20]).…”
mentioning
confidence: 99%